2021
DOI: 10.1038/s41598-021-98969-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transmission of respiratory infections within but not between mountain gorilla groups

Abstract: Minimizing disease transmission between humans and wild apes and controlling outbreaks in ape populations is vital to both ape conservation and human health, but information on the transmission of real infections in wild populations is rare. We analyzed respiratory outbreaks in a subpopulation of wild mountain gorillas (Gorilla beringei beringei) between 2004 and 2020. We investigated transmission within groups during 7 outbreaks using social networks based on contact and proximity, and transmission between gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 62 publications
2
42
0
Order By: Relevance
“…For example, increased group density is associated with increased intergroup interactions 42 , 43 , which presumably would enhance the opportunity for COVID-19 to pass from one group to another, thus increasing R 0 . The potential transmission of diseases like COVID-19 between social groups is an important area of future study (for respiratory diseases on this population see 44 . Nonetheless, our finding that there is a threshold value of R 0 = 1.05 above which the subpopulations start declining highlights the current risk of an outbreak on the subpopulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, increased group density is associated with increased intergroup interactions 42 , 43 , which presumably would enhance the opportunity for COVID-19 to pass from one group to another, thus increasing R 0 . The potential transmission of diseases like COVID-19 between social groups is an important area of future study (for respiratory diseases on this population see 44 . Nonetheless, our finding that there is a threshold value of R 0 = 1.05 above which the subpopulations start declining highlights the current risk of an outbreak on the subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the longer term, minimizing R 0 in mountain gorillas could involve decreasing the frequency of group interactions 44 , by minimizing any risk of human disturbance to existing habitat allowing groups to spread out to the maximum extent and also expanding the park.…”
Section: Discussionmentioning
confidence: 99%
“…Bonobos that never exhibited symptoms were considered to be healthy and non-infected during the study period (cf. [ 57 , 58 ]; see Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, respiratory disease is a major cause of morbidity and mortality in both captive and wild primate populations and thus a prominent threat to general primate welfare [ 40 , 42 , 43 , 54 , 55 , 56 ]. To date, only two studies have investigated the link between SNA measures and the occurrence of respiratory disease in primates [ 57 , 58 ]. One study found no association between the social network and respiratory disease in mountain gorillas ( Gorilla beringei beringei ) [ 57 ], while another study showed that in chimpanzees, males with higher strength in a proximity network had a higher chance of showing symptoms of respiratory disease, indicating the vital role of the social-proximity network in the spread of the pathogen in the group [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation